Macrophage targeted polymeric curcumin nanoparticles limit intracellular survival of Mycobacterium tuberculosis through induction of autophagy and augment anti-TB activity of isoniazid in RAW 264.7 macrophages - Gupta, Pramod Kumar; Jahagirdar, Priyanka; Tripathi, Devavrat; Devarajan, Padma V.; Kulkarni, Savita (Frontiers in Immunology, 2023)
Rapid emergence of antibiotic resistance in tuberculosis has left us with limited resources to treat and manage multi drug resistant (MDR) cases of tuberculosis, prompting the development of novel therapeutics. Mycobacterium tuberculosis (MTB) perturbs the host protective pathways for its survival, therefore host directed therapeutic (HDT) interventions offer an attractive alternative strategy. Curcumin (CMN), the principle curcuminoid from Curcuma longa is known to have anti-TB activity against MDR strains of MTB in macrophages. We discovered that treatment of CMN induced autophagy in uninfected and MTB infected macrophages which was evident by conversion of LC3-I to LC3-II and degradation of p62. Inhibition of autophagy by a pharmacological inhibitor 3-MA resulted in significant inhibition of intracellular killing activity of CMN, suggesting the involvement of autophagy in intracellular clearance of MTB. Moreover, annexin V-FITC/PI staining data suggested induction of apoptosis in uninfected and MTB infected macrophages post CMN treatment. This finding was further corroborated by upregulated expression of pro-apoptotic proteins, Bax, cleaved caspase-3 and PARP and diminished expression of anti-apoptotic protein Bcl-2 as evaluated by immunoblotting. Using GFP-MTB H37Rv and Lysotracker Red staining we demonstrated co-localization of GFP-MTB H37Rv containing phagosome to lysosome after CMN treatment, indicating enhanced phagosome lysosome fusion. Due to poor bioavailability of CMN, its clinical use is limited, therefore to overcome this issue, CMN was encapsulated in Poly(lactic-co-glycolic) acid (PLGA) shell, resulting in polymeric CMN nano particles (ISCurNP). Flow cytometric evaluation suggested >99% uptake of ISCurNP after 3h of treatment. In BALB/c mice, oral dose of ISCurNP resulted in 6.7-fold increase in the bioavailability compared to free CMN. Moreover, ISCurNP treatment resulted in significant decrease in the intracellular survival of MTB H37Rv through induction of autophagy. Adjunct action of ISCurNP and CMN in combination with isoniazid (INH) revealed >99% decrease in intracellular survival of MTB in macrophage as compared to ISCurNP, CMN or INH alone.In conclusion, our findings suggest the role of ISCurNP as novel host directed formulation to combat both sensitive and MDR strains of MTB by induction of autophagy.